Synthesis of Zeolite Y from Kaolin via hydrothermal method - Krongkrachang, Pimpetch; Thungngern, Pimpreeya; Asawaworarit, Panuruj; Houngkamhang, Nongluck; Eiad-Ua, Apiluck (My University, 2019)
ZeoliteY has been successfully synthesized via a two-step hydrothermal method with kaolin from Lampang province as a precursor. For the first hydrothermal, kaolin with an addition of sodium silicate (NaSi3O7) or tetraethyl orthosilicate (TEOS) was mixed with sodium hydroxide (NaOH) and autoclaved for 200oC at different reaction times for 6, 8 and 10 h, respectively. Sodium hydroxide and hydrochloric acid were added into the compound mixture to adjust its pH before it was formed into gel. After a second time hydrothermal at 90°C for 2 days, the solid product was filtered out, washed by deionized water and dried overnight. The zeolite was then characterized by X-ray diffraction spectroscopy (XRD) to identify type and crystallization, scanning electron microscopy (SEM) for morphology, Fourier transform infrared spectroscopy (FTIR) to identify its functional group and N2 adsorption to study the adsorption/desorption isotherm and pore distribution. From N2 adsorption-desorption isotherm, it is revealed that the zeolite obtained by this method have 571 m2/g surface area and pore size distribution around 4.89 nm.
Keywords: Hydrothermal; Kaolin; Sodium silicate; Tetraethyl orthocilicate; Zeolite Y